Pengembangan Soal Pengayaan Matematika Online untuk Siswa Kelas X - Yanna Sanova; Zulkardi Zulkardi; Yusuf Hartono (Universitas Hamzanwadi, 2017)
The purpose of this study is to produce problems enrichment math for the 10th grade Senior High School to train high-level thinking is valid and practical as well as determine the effect of potential problems math enrichment for the 10th grade that has been developed on the results of students' mathematics learning SMA Negeri 1 Palembang. The subjects were all students in 10th grade SMAN 1 Palembang. The method used is research development or Development Reserch through three stages: preliminary (preparatory stage and phase of development issues), formative evaluation or prototyping stage (stage of evaluation and revision phase) and the assessment stage. During the preparation stage (preliminary) conduct a review of the curriculum, determine the place and the subject of research, reviewing some of the literature, do designing item that will be developed. The item has the characteristics about the non routine, problematic, demanding reasoning, containing an association, or demanding communication skills do with prototyping. The next stage of formative evaluation: (1) self evaluation, (2) Expert Review, (3) one - to - one evaluation, (4) small group and (5) field test. Criteria for the success of this study is the product obtained in the form about math enrichment for 10th grade valid and practical and has a potential effect. Prototype devices were developed about categorized valid and practical. Valid qualitatively illustrated by the results of the assessment validator, where almost all validators declared either by the content, construct and language. Valid quantitatively based analysis of items (the validity of the items) and practically drawn from the test results, which students can use the device with a good question (context recognizable, readable, does not give rise to a double interpretation, and according to the student's train of thought). Problem produced a total of 18 questions. The problems spread to the cognitive level of 3 to 5. Based on the development process is to be obtained that the prototype device developed about who has had the potential effects on the learning outcomes of high school students, it is seen from the test results about math enrichment to the learning outcomes of students with 32% category of excellent, 44% good category, 13% adequate and 3% less category.